Objective Impact of Hematology-Oncology Hospitalist Care in an Inpatient Setting. Issue 10 (19th October 2022) - Fanucci, Kristina A.; Yang, Andrew; Chambers, Alison; Dizon, Don; Safran, Howard; Niroula, Rabin
Abstract : PURPOSE: The utilization of the hospitalist care model has increased over the past decade because of improved cost-effectiveness, quality of care, and value that it provides. Studies have shown that compared with the traditional care model, use of hospitalists provides cost-saving and improved value to hospital systems. However, the data for the use of oncology hospitalists (ONC Hosp) are sparse. In this study, we investigate the impact of inpatient ONC Hosp on 30-day readmissions, length of stay (LOS), discharge to hospice, and inpatient mortality when compared with a traditional model where outpatient oncologists manage the acute issues of hospitalized patients with cancer. METHODS: Rhode Island Hospital hired ONC Hosps to attend on the inpatient oncology service. To determine the impact of this new patient care model, we performed a retrospective review of oncology patients admitted to Rhode Island Hospital between July 1, 2012, and June 30, 2018, and compared quality outcomes of 30-day readmission, LOS, discharge to hospice, and inpatient mortality to those from the traditional care model. RESULTS: Compared with outpatient oncologists care, care by ONC Hosp was associated with a significant decrease in 30-day readmissions (23.0% v 29.6%, P = .019) and a significant increase in discharge to hospice (18.1% v 12.1%, P < .001). No significant difference was detected between LOS ( P = .833) or inpatient mortality ( P = .332). CONCLUSION: This study shows that compared with the traditional care model, the use of ONC Hosps has a positive impact on patient care and the potential to add value to the hospital system.